2002
DOI: 10.1002/cncr.10899
|View full text |Cite
|
Sign up to set email alerts
|

Expression and immunogenicity of a tumor‐associated antigen, 90K/Mac‐2 binding protein, in lung carcinoma

Abstract: BACKGROUNDThe authors attempted to obtain shared proteins among lung carcinoma cells by column chromatographies. A glycoprotein with approximately 500 kDa isolated from QG56 cells showed an identical amino acid sequence to 90K/Mac‐2 binding protein (M2BP). This protein has been reported to be highly expressed and to modulate the expression of surface molecules involved in immune responses on cultured cancer cells. Therefore, it would be beneficial for M2BP to be targeted in cancer immunotherapy.METHODSThe auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…These results were also shown for breast cancer, where Mac-2BP levels were associated with poor prognosis, presence of metastasis in liver, and shorter disease-free interval (Iacobelli et al, 1994). Elevated levels of this protein have also been shown in lung carcinoma (Ozaki et al, 2002), correlating strongly with clinical staging (Ozaki et al, 2004a).…”
Section: Mac-2 Binding Protein: a Tumor-associated Antigenmentioning
confidence: 55%
“…These results were also shown for breast cancer, where Mac-2BP levels were associated with poor prognosis, presence of metastasis in liver, and shorter disease-free interval (Iacobelli et al, 1994). Elevated levels of this protein have also been shown in lung carcinoma (Ozaki et al, 2002), correlating strongly with clinical staging (Ozaki et al, 2004a).…”
Section: Mac-2 Binding Protein: a Tumor-associated Antigenmentioning
confidence: 55%
“…Galectin-3-binding protein is a secreted 90 kDa Nglycosylated protein with affinity for galectins as well as extracellular matrix proteins [12]. Sudden increase in serum galectin-3-binding protein levels have been reported in various infectious and cancerous diseases, including hepatitis C [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…12,13 It has been proposed that the interaction between these proteins may enhance the growth and biological behavior of cancer cells. In cancerous tissues, 90K is expressed at high levels [14][15][16] and is associated with poor prognosis. [16][17][18] Immunohistochemical analyses of 90K expression have revealed weak or no expression in most normal tissues and strong upregulation in tumor cells of human neoplastic tissues, 19 suggesting that 90K can be used as a target antigen in cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In cancerous tissues, 90K is expressed at high levels [14][15][16] and is associated with poor prognosis. [16][17][18] Immunohistochemical analyses of 90K expression have revealed weak or no expression in most normal tissues and strong upregulation in tumor cells of human neoplastic tissues, 19 suggesting that 90K can be used as a target antigen in cancer immunotherapy. Ulmer et al 20 demonstrated that immunohistochemical analyses of colon tumors showed elevated expression of 90K in all tumor samples compared to normal colon samples.…”
Section: Introductionmentioning
confidence: 99%